2015
DOI: 10.1161/atvbaha.114.305028
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Interleukin-1 Receptor–Associated Kinase-1 in Vascular Smooth Muscle Cell Proliferation and Neointimal Formation After Rat Carotid Injury

Abstract: To investigate the consequences of hybridization between species, we studied three replicate hybrid populations that formed naturally between two swordtail fish species, estimating their fine-scale genetic map and inferring ancestry along the genomes of 690 individuals. In all three populations, ancestry from the "minor" parental species is more common in regions of high recombination and where there is linkage to fewer putative targets of selection. The same patterns are apparent in a reanalysis of human and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 77 publications
0
32
0
2
Order By: Relevance
“…An earlier study in mice showed that IRAK1 deletion attenuates atherosclerosis progression [20]. Recent work from our laboratory also demonstrated the role of IRAK1 in rats VSMCs proliferation, an important event in atherosclerosis progression [38]. At the same time enhanced expression of IRAK1 is observed in human atherosclerotic arteries [18].…”
Section: Discussionmentioning
confidence: 77%
“…An earlier study in mice showed that IRAK1 deletion attenuates atherosclerosis progression [20]. Recent work from our laboratory also demonstrated the role of IRAK1 in rats VSMCs proliferation, an important event in atherosclerosis progression [38]. At the same time enhanced expression of IRAK1 is observed in human atherosclerotic arteries [18].…”
Section: Discussionmentioning
confidence: 77%
“…Moreover, blocking the progress of atherosclerosis by inhibiting TLR4-mediated signalling has been verified in different animal models [22-25]. LPS has been shown to activate TLR4 and induce various signalling cascades, including PI3K/Akt [13], mitogen-activated protein kinase [26, 27] and interleukin-1 receptor associated kinase (IRAK) [28, 29]; each of which participates in cell proliferation [30]. However, the underlying molecular mechanisms controlling VSMCs proliferation after LPS stimulation remain to be identified.…”
Section: Discussionmentioning
confidence: 99%
“…5C and D). However, others have shown that the silencing of PKC-ε inhibited PDGF-induced ERK 1/2 phosphorylation, indicating that PKC-ε is up-stream of ERK [32]. Regardless of the hierarchy or parallel role of PKC-ε in regulating cell proliferation in relation to ERK, the data presented in Fig.…”
Section: Discussionmentioning
confidence: 79%
“…A recent study by Jain et al [32] showed an increase in the proliferation of rat VSMCs in an endogenous interleulin-1 receptor-associated kinase-1 (IRAK)-ERK-PKC-ε-dependent manner in a rat balloon injury model. The present data indicate that the phosphorylation of ERK in VSMCs was increased by PMA in a rapid and transient manner.…”
Section: Discussionmentioning
confidence: 99%